2013
DOI: 10.1002/ange.201205998
|View full text |Cite
|
Sign up to set email alerts
|

Weak Te,Te Interactions through the Looking Glass of NMR Spin–Spin Coupling

Abstract: Most of the tools for quantifying the extent of chemical bonding between two atoms are quantum-chemical in nature. None of them are unambiguous, however, and different analyses can lead to conflicting interpretations, even concerning the most fundamental question of whether or not atoms are linked by a chemical bond. [1,2] One of the indicators that can be probed experimentally is the indirect spin-spin coupling constant (SSCC). For instance, observation of spinspin coupling across hydrogen bonds [3] has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 32 publications
11
26
0
Order By: Relevance
“…This value is comparable to those of related systems such as Acenap(P i Pr 2 )(SnPh 3 ) or Acenap(TePh) 2 (Acenap=acenaphthene‐5,6‐diyl), where the onset of the 3c–4e bonding between the formally non‐bonded atoms has been shown through the sizable J ( 31 P– 119 Sn) or J ( 125 Te– 125 Te) coupling constants 32. 34 Unfortunately, the unfavourable properties of the NMR‐active antimony isotopes ( 121 Sb and 123 Sb), in particular their high quadrupolar moments, prevent the use of direct PSb NMR probe in this series. On the other hand, compound 4 displays large magnitude (40.1 Hz) of a 31 P 13 C coupling involving the ipso ‐carbon from a phenyl group on the antimony atom (atom C13 in Figure 2, hence formally 5ts J CP ).…”
Section: Resultssupporting
confidence: 77%
“…This value is comparable to those of related systems such as Acenap(P i Pr 2 )(SnPh 3 ) or Acenap(TePh) 2 (Acenap=acenaphthene‐5,6‐diyl), where the onset of the 3c–4e bonding between the formally non‐bonded atoms has been shown through the sizable J ( 31 P– 119 Sn) or J ( 125 Te– 125 Te) coupling constants 32. 34 Unfortunately, the unfavourable properties of the NMR‐active antimony isotopes ( 121 Sb and 123 Sb), in particular their high quadrupolar moments, prevent the use of direct PSb NMR probe in this series. On the other hand, compound 4 displays large magnitude (40.1 Hz) of a 31 P 13 C coupling involving the ipso ‐carbon from a phenyl group on the antimony atom (atom C13 in Figure 2, hence formally 5ts J CP ).…”
Section: Resultssupporting
confidence: 77%
“…In their study of corresponding selenium derivatives, Nakanishi and colleagues concluded that this small energy difference must result in an equilibrium existing between the AB and CC t conformers in solution 9. This hypothesis was supported in our own study, in which the experimentally observed J value for Acenap(TePh) 2 (2110 Hz; G , Figure 1) was found to lie intermediate between the predicted 4 J ( 125 Te, 125 Te) SSCCs for the two conformers (CC t 2604 Hz; AB 1543 Hz) 11…”
Section: Introductionsupporting
confidence: 72%
“…Our own detailed conformational analyses of the related bis(tellurium) compound Nap(TeMe) 2 ( F , Figure 1) revealed a similar conformational dependence of 4 J (Te,Te) through‐space coupling, with a dramatic change in the magnitude of 4 J (Te,Te) SSCCs predicted upon subtle changes to the structural conformation 11. The optimised CC t conformer (vide infra) is the global minimum and is predicted to have 4 J ( 125 Te, 125 Te) values around 2500 Hz, whilst a conformer in the AB region is predicted to have a much lower J value (ca.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations